Study of Small-Scale Drilling under Different Material Hardness and Machine RPM - Syamsul Hidayat; Melinda Dwi Erintina (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Small-scale drilling experiments are designed to represents field blasthole-drilling conditions therefore it can be used to support decision-making process in mining operations. This study is a laboratory-scale drilling investigation, conducted to determine the penetration rate and the appearance of drilling dust clouds under varying material hardness and engine RPM (revolution per minute). Drilling was carried out on concrete media using bench drilling equipment under 7 (seven) different conditions based on material hardness and RPM. Data on drilling speed, drilling time and penetration rate were used for analysis and to support the conclusion. The results indicated that the penetration rate in soft material is faster than in hard material. The increase in penetration rate occurs proportionally with the increase of RPM in soft material. In hard material, significant differences in penetration rate occur in drilling under slow and medium RPM, whereas there is no significant difference in penetration rates between drilling under medium and high RPM. In hard materials, there exist a